Oral Health Status of Workers in Lead Battery Manufacturing Units in Udaipur City: A Cross-Sectional Comparitive Study - Deora, Shorabh; Oza, Swapnil; kakadiya, Jignesh; Bishnoi, Manish; Pansuriya, Aniket; Khubchandani, Pooja (Journal of Neonatal Surgery, 2025)
Background: Every person's oral health is an important aspect of their overall health and a valuable asset. In India, the majority of working people are often from lower socioeconomic groups. Aim: To evaluate the oral health status of workers in lead battery manufacturing units in Udaipur city. Methodology: Following their fulfilment of the study's requirements, 900 individuals were chosen. The study was cross-sectional, and the pre-validated proforma was used to gather the necessary data. This proforma contained information on demographics (age, sex, bad habits, consumption of acidic foods, etc.), as well as hard and soft tissue examinations. The latter included information on extraoral alterations, dental caries status, oral mucosal disorders, periodontal state, and fluorosis status. The data was gathered using the WHO Oral Health Assessment form from 1997. The degree and presence of tooth erosion in the sampled workers were evaluated during the oral examination between July 20, 2021, and September 25, 2021, using the Basic Erosive Wear Examination (BEWE) scoring method. The descriptive statistics were applied along with Chi-square test using the SPSS (version 20). Results: The results indicated male prevalence of the age 25-35 years, with many consuming smoking and drinking, acidic food and drinks, reduced use of toothbrush based on the SES that they belonged. Treatment was required for trauma, prosthetics, restoration, and fluorosis among the study population. SES was directly correlated with dental usage, bad behaviours, dentition state, and treatment requirements. Conclusion: The SES and the dental treatment needs are directly related to one another. Lower the socio-economic group, more neglected the unmet dental treatments and awareness.